Perangkat Penentu Kualitas Beras Ditinjau dari Kadar Air dan Berat Butir Menir Berbasis Arduino Uno - Mustofah, Mustofah; Utami, Pipit (Elinvo (Electronics, Informatics, and Vocational Education), 2019)
Determining the quality of rice is something that must be done to maintain the quality of rice produced by farmers. Quality determinants used for this process can be relied on for rice properly and efficiently. Determination of air content using soil moisture sensor yl-69 and determination of grain weight using a load cell sensor that emits with an Arduino UNO microcontroller as a device controller device. System making method consists of needs, analytic requirements, block diagrams, system design, manufacturing tools, testing tools and tools. The test results show that the determinant of rice quality in terms of good air and weight with errors in the readings of soil moisture sensor yl-69 is 1.522% and the error in load cell reading is 0.431%. The performance of this rice quality assessment device shows that the device can function properly in terms of the sensor's working measurement, the device for determining rice quality and the performance of all components in the device can run well.